Pelvic Actinomycosis - Alejandra García-García; Ninfa Ramírez-Durán; Horacio Sandoval-Trujillo; María del Socorro Romero-Figueroa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Actinomycosis is a chronic bacterial infection caused by Actinomyces, Gram-positive anaerobic bacteria. Its symptomatology imitates some malignant pelvic tumours, tuberculosis, or nocardiosis, causing abscesses and fistulas. Actinomycoses are opportunistic infections and require normal mucous barriers to be altered. No epidemiological studies have been conducted to determine prevalence or incidence of such infections. Objective. To analyse the clinical cases of pelvic actinomycosis reported worldwide, to update the information about the disease. Methods. A systematic review of worldwide pelvic actinomycosis cases between 1980 and 2014 was performed, utilising the PubMed, Scopus, and Google Scholar databases. The following information was analysed: year, country, type of study, number of cases, use of intrauterine device (IUD), final and initial diagnosis, and method of diagnosis. Results. 63 articles met the search criteria, of which 55 reported clinical cases and 8 reported cross-sectional studies. Conclusions. Pelvic actinomycosis is confusing to diagnose and should be considered in the differential diagnosis of pelvic chronic inflammatory lesions. It is commonly diagnosed through a histological report, obtained after a surgery subsequent to an erroneous initial diagnosis. A bacterial culture in anaerobic medium could be useful for the diagnosis but requires a controlled technique and should be performed using specialised equipment.